Resistance of Panonychus citri (McGregor) (Acari: Tetranychidae) to pyridaben in China: monitoring and fitness costs. Issue 3 (16th November 2022) - Pan, Deng; Xia, Meng‐Hao; Luo, Qiu‐Juan; Liu, Xun‐Yan; Li, Chuan‐Zhen; Yuan, Guo‐Rui; Wang, Jin‐Jun; Dou, Wei
Abstract: Background: Panonychus citri is a major citrus pest worldwide. The short life cycle and high reproductive potential of P. citri, combined with heavy acaricide use, have led to high levels of resistance to acaricides, posing a threat to global resistance management programs. Here, resistance monitoring was established to determine the pyridaben resistance status of ten P. citri populations in China from 2014 to 2021 using a leaf‐dipping assay. Four characterized strains—the susceptible strain (Lab_S), the resistant strain (Pyr_R), as well as the segregated resistant strain (Pyr_Rs) and the segregated susceptible strain (Pyr_Control) derived from the crossing of the Lab_S and Pyr_R strains, were used to evaluate the life‐history characteristics using age‐stage, two‐sex life tables. Results: Most P. citri populations developed high resistance to pyridaben. Resistance levels exceeded 1000‐fold in Yuxi, Anyue, Nanning, and Ganzhou populations compared with the Lab_S strain. Compared with Pyr_Control, two key fitness cost criteria, developmental period and fecundity, showed significant differences in Pyr_Rs under consistent conditions. The intrinsic rate of increase, net reproductive rate and gross reproductive rate were lower in the resistant strain compared with the Pyr_Control strain. The Pyr_Rs strain had a lower relative fitness of 0.934 compared with the Pyr_Control. Moreover, the life‐history traits and population parameters of the Pyr_R strain also showed significant differences compared with the Lab_S strain. Conclusion: The resistance levels to pyridaben varied greatly among the different P. citri populations and showed regional differences. Substantial fitness costs are associated with pyridaben resistance. This study provides potential implications for developing strategies for resistance management in P. citri . © 2022 Society of Chemical Industry. Abstract : Most Panonychus citri populations developed high resistance to pyridaben in China between 2014 and 2021. Segregating susceptible and resistant strains were established, and the Pyr_R and Pyr_Rs strains incurred significantly lower relative fitness costs of 0.952 and 0.934, when compared with the Lab_S and Pyr_Control strains, respectively.